Empowering Counselor Team Construction in Higher Vocational Colleges with Educator Spirit: Logical Approaches, Value Implications, and Practical Paths - Mou, Yurui (Journal of Research in Vocational Education, 2026)
Educator spirit contains unique Chinese educational heritage and cultural genes. Promoting and practicing educator spirit is of great significance to building a high-quality counselor team in higher vocational colleges. From the perspective of policy logic, educator spirit is synergistic with the mission of high-quality development of higher vocational education; from practical logic, educator spirit is precisely compatible with the professional literacy of higher vocational counselors; from development logic, there is a two-way coupling between educational and cultural inheritance and teachers’ professional spirit. Empowering with educator spirit can foster the educational sentiment, refine professional literacy, consolidate ideological foundation and improve education effectiveness of counselors in higher vocational colleges. Based on this, it is proposed to improve the quality and efficiency of counselor team construction in higher vocational colleges by gathering common vision, improving mental models, driving self-transcendence and promoting team learning through educator spirit.